Manejo agronómico de la Moringa (Moringa oleífera); para el uso forrajero en el Ecuador - Oquendo González, Santiago Efraín (2022)
Moringa oleifera is found in arid and semi-arid zones, with great resistance to droughts, since its adaptation is great in different environments. Today the attention to these trees is very great in tropical countries, Latin America, the Caribbean and Asia. In Ecuador in 2009 its development was given by its favorable benefits and has been included in different parts of the country. It has a facility to develop from seeds or cuttings, its fruit is a pod similar to a legume that contains 12 to 25 seeds. Moringa as a forage species is of great economic importance for feeding cattle and pigs. This crop provides many benefits and not only to be used as a food resource for animals, but also to develop medicinal products. Stems, leaves and branches have medicinal and protein properties with an index of 226.0 to 268.0 g in dry matter and this helps improve the living conditions of animals. It adapts very quickly to the edaphoclimatic factors of the continents and responds with good vigor, which means that it has a high number of leaves that can be collected and supplemented to give to animals. Its cultivation is growing nationally and worldwide, its discovery helped at all levels, being one more implement for animal feed, which is what is sought every day to innovate and enhance its production.